Trajectories of Mother-Infant Communication: An Experiential Measure of the Impacts of Early Life Adversity - Granata, Lauren; Valentine, Alissa; Hirsch, Jason L.; Honeycutt, Jennifer; Brenhouse, Heather (Frontiers in Human Neuroscience, 2021)
Caretaking stability in the early life environment supports neurobehavioral development, while instability and neglect constitute adverse environments that can alter maturational processes. Research in humans suggests that different types of early life adversity (ELA) can have differential effects on caretaker relationships and later cognitive and social development; however identifying mechanistic underpinnings will require animal models with translational validity. Two common rodent models, maternal separation (MS) and limited bedding (LB), influence the mother-infant relationship during a critical window of development. We hypothesized that these paradigms may affect the development of communication strategies on the part of the pup. Ultrasonic vocalizations (USVs) are a care-eliciting mechanism and ethologically relevant response to stressors in the rat pup. USV emission rates and acoustic parameters change throughout early development, presenting the opportunity to define developmental milestones in USVs that would reflect neurobehavioral aberrations if disrupted. This study investigated the effects of MS or LB on the dam-pup relationship by quantifying pup USVs, maternal behavior, and the relationship between the two. First, we used a generalized additive model approach to establish typical developmental trajectories of USV acoustic properties and determine windows of change in MS or LB rearing. Additionally, we quantified maternal behaviors and the predictability of maternal care sequences using an entropy rate calculation. MS and LB each shifted the developmental trajectories of USV acoustic parameters and call types in a sex-specific manner. MS more often impacted male USVs, while LB impacted female USVs. MS dams spent more time passive nursing, and LB dams spent more time on the nest. The predictability of maternal care was associated with the rate of USV emissions exclusively in females. Taken together, findings demonstrate sex- and model-specific effects of rearing environments on a novel developmental trajectory involving the mother-infant relationship, facilitating the translation of animal ELA paradigms to assess later-life consequences.